Barriers to on-line learning the experience of the Scottish Executive Business Development Unit - Bothams, John F.; Fordyce, Lesley (Proceedings of the International Conference on Networked Learning, 2002)
This paper discusses the experience of the Scottish Executive's Business Development Unit when the individuals within the Unit were introduced to online learning as a knowledge exchange facility and vehicle for development of both individuals and the professional Unit. It describes the approach adopted in partnership with the University of Strathclyde Graduate School of Business. In particular, it explores the difficulties associated with making on-line learning a reality in an already established community. It also discusses the remedial action taken in an attempt to develop a solution to address the cultural, personal and environmental barriers to on-line learning cited by individuals within the community. In total it provides a useful comparator for other networked communities.